Pemekaran Daerah dan Otonomi Daerah Kerangka Hubungan Pusat Daerah - Kusuma, Winanda; Sintasari, Sieska Afriana (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
Regional autonomy as the government's choice in the administration of regional government to assist efficient and effective regional governments in managing governance. The desantralization pattern distributes authority to the regions within territorial limits. The fundamental organization enables the governing policies of a system. A policy itself in the whole system of government. The pattern of power and financial relations between the central government and regional governments is largely determined by the national political configuration at a given time. This article was written using the method of conceptual thinking with critical legal studies as the type of research. The result of this article is that the formation of new regions must be aimed at improving public services, accelerating the realization of community welfare, and also channeling political education at the local level. There is also a need for an evaluation of regional expansion with indicators of the objectives of the expansion. The urgency of evaluation is so that the desire and rapid division of regions does not make local governments paradoxical with goals. it is necessary to implement it as a corrective action so that the positive implications of corrective action can be felt more properly, it must have a legal basis by the provider of regional autonomy, namely the central government.